Influence of Total Hysterectomy to Sexual Function: Pengaruh Histerektomi Total dengan Fungsi Seksual - Andini Z. Dini; Ferry Yusrizal; Firmansyah Basir; Theodorus (Indonesian Journal of Obstetrics and Gynecology, 2022)
Objective: To determine whether there are differences the impact of total hysterectomy on sexual function between each woman. Women who perform total hysterectomy often experience fear of the negative effects of hysterectomy on their sexual function.Methods: Randomized clinical trials have been conducted in outpatient clinic Obstetrics and Gynecological wards of Dr. Muhammad Hoesin General Hospital, Palembang from February to October 2020. There were 40 samples of women undergoing a total hysterectomy met the inclusion criteria. Sexual function before and after hysterectomy was analyzed with the Wilcoxon test. Data analysis using SPSS version 22.0.Results: This study showed decreased of desire, decreased stimuli, decreased orgasm, increased lubrication, increased sexual satisfaction, and increased dyspareunia samples after a total hysterectomy. However, with statistical analysis obtained results there were no meaningful changes in sexual function of desire (p = 0.849), stimuli (p = 0.716), lubrication (p = 0.261), orgasm (p = 0.839), sexual satisfaction (p = 0.613) and dyspareunia (p = 0.510) after total hysterectomy .Conclusion: It can be concluded that there is no significantly total hysterectomy effect on sexual function, based on FSFI (sexual desire, sexual arousal, lubrication, orgasm, sexual satisfaction, and pain.Keywords: clinical trial, FSFI, hysterectomy, sexual function. Abstrak Tujuan: Mengetahui adakah perbedaan dampak histerektomi total pada fungsi seksual antara setiap perempuan. Perempuan yang melakukan histerektomi total sering mengalami ketakutan akan efek negatif histerektomi pada fungsi seksualnya. Metode: Telah dilakukan uji klinis secara acak di poliklinik rawat jalan bangsal Obstetri dan Ginekologi RSUP Dr. Muhammad Hoesin Palembang dari bulan Februari sampai Oktober 2020. Sebanyak 40 sampel perempuan yang menjalani histerektomi total memenuhi kriteria inklusi. Fungsi seksual sebelum dan sesudah histerektomi dianalisis dengan uji Wilcoxon. Analisi data menggunakan SPSS versi 22.0.Hasil: Penelitian ini menunjukkan penurunan hasrat, penurunan rangsangan, penurunan orgasme, peningkatan lubrikasi, peningkatan kepuasan seksual, dan peningkatan dispareunia setelah histerektomi total. Namun dengan analistik statistik didapatkan hasil tidak ada perubahan yang bermakna pada fungsi seksual yaitu hasrat (p=0,849), rangsangan (p=0,716), lubrikasi (p= 0,716), lubrikasi (p=0,261), orgasme (p=0,839), kepuasan seksual (p= 0,613), dan dispareunia (p= 0,510) setelah histerektomi total.Kesimpulan: Dapat disimpulkan bahwa tidak ada pengaruh histerektomi total yang signifikan terhadap fungsi seksual berdasarkan FSFI (hasrat, seksual, gairah seksual, lubrikasi, orgasme, kepuasan seksual, dan nyeri.Kata kunci: fungsi seksual, FSFI, histerektomi, uji klinis.